Cardiac Fibroblasts and Myocardial Regeneration - Chen, Wangping; Bian, Weihua; Zhou, Yang; Zhang, Jianyi (Frontiers in Bioengineering and Biotechnology, 2021)
The billions of cardiomyocytes lost to acute myocardial infarction (MI) cannot be replaced by the limited regenerative capacity of adult mammalian hearts, and despite decades of research, there are still no clinically effective therapies for remuscularizing and restoring damaged myocardial tissue. Although the majority of the cardiac mass is composed of cardiomyocytes, cardiac fibroblasts (CFs) are the most numerous cells in the heart and the primary drivers of fibrosis, which prevents ventricular rupture immediately after MI but the fibrotic scar expansion and LV dilatation can eventually lead to heart failure. However, embryonic CFs produce cytokines that can activate proliferation in cultured cardiomyocytes, and the structural proteins produced by CFs may regulate cardiomyocyte cell-cycle activity by modulating the stiffness of the extracellular matrix (ECM). CFs can also be used to generate induced-pluripotent stem cells and induced cardiac progenitor cells, both of which can differentiate into cardiomyocytes and vascular cells, but cardiomyocytes appear to be more readily differentiated from iPSCs that have been reprogrammed from CFs than from other cell types. Furthermore, the results from recent studies suggest that cultured CFs, as well as the CFs present in infarcted hearts, can be reprogrammed directly into cardiomyocytes. This finding is very exciting as should we be able to successfully increase the efficiency of this reprogramming, we could remuscularize the injured ventricle and restore the LV function without need the transplantation of cells or cell products. This review summarizes the role of CFs in the innate response to MI and how their phenotypic plasticity and involvement in ECM production might be manipulated to improve cardiac performance in injured hearts.